Kajian Teoritis atas Pemikiran Nurcholish Madjid tentang Rekonstruksi Kurikulum Pesantren - Rizky Umar Hasan; Shofiana Nurul Azkiya; Zeniar Nur Aulia; Fauzan Anis Sahara (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
This study aims to examine Nurcholish Madjid’s ideas on the reconstruction of pesantren curricula in facing the challenges of modernity. As traditional Islamic educational institutions, pesantren are often criticized for focusing heavily on fiqh and linguistic sciences, while modern society requires the integration of general knowledge, technology, and life skills. Using a qualitative method with a library research approach, data were obtained from Nurcholish Madjid’s Bilik-Bilik Pesantren and related academic literature. The findings highlight three main issues in Cak Nur’s thought: (1) critique of the unbalanced traditional curriculum, (2) the gap between pesantren and the modern world, and (3) the need for reformulating a universal, rational, and inclusive Islamic weltanschauung. These ideas emphasize that pesantren curricula must balance tradition and modernity, strengthen faith and spirituality, while also fostering critical thinking, scientific literacy, and social ethics. The implication of this study suggests that integrative curricula are essential for pesantren to remain relevant in the era of globalization.